Que fait l’Intelligence Artificielle à l’intelligence ? - Eugène Favier-Baron (Appareil)
This article will consider Artificial Intelligence as a « dispositif naturalisé » in the sense of Yves Jeanneret, i.e. as a means of reifying a certain interpretation of human cognitive mechanisms, which in turn become a point of reference for what should be perceived as the characteristics of human intelligence. AI, revealing in this the ambiguity of the analogy that founds it, proceeds as an artifice of a modeling and thus of a degradation of reality. This modeling is however posed in nature when it resurfaces in return on our expectations in terms of human intelligence. This process is as much about the materiality of intelligent algorithms as a technical medium, as it is about their mediality as a « Être culturel » that gains, for the designers as well as the users of AI, a certain semiological autonomy. The aim is to criticize the epistemological premises of this modeling as well as to analyze its political consequences.